Altered upper respiratory tract microbiota in laryngeal cough attributed to lung yin deficiency and the modulatory effects of Yangyin Qingfei Oral Liquid - Yu, Fei; Jin, Jing; Jin, Xinlai; Ding, Xuchun; Lou, Yafang (Frontiers in Microbiology, 2025)
ObjectiveThis study investigates changes in upper respiratory tract microbiota in laryngeal cough patients with lung yin deficiency using high-throughput sequencing of the 16S rDNA gene. It also examines the modulatory effects of Yangyin Qingfei Oral Liquid (YYQFOL).MethodsWe included 100 laryngeal cough patients and 65 healthy subjects, collecting throat swab samples for microbiota comparison. Patients were randomly assigned to a control group receiving methoxyphenamine capsules and an experimental group receiving YYQFOL and methoxyphenamine for 10 days. We assessed changes in microbiota, symptom scoring, and Leicester Cough Questionnaire (LCQ) results. Each group was divided into responders (R) and non-responders (NR).ResultsPatients with laryngeal cough had significantly lower microbial abundance and diversity than healthy subjects (p < 0.05). After treatment, symptom scores and LCQ results improved significantly (p < 0.05), with responders in the experimental group (ER) showing significantly better improvement than those in the responders in the control group (CR) (p < 0.05). Post-treatment, the experimental group saw a significant reduction in Streptococcus, Haemophilus, and other genera, while Veillonella increased (p < 0.05).ConclusionLaryngeal cough patients with lung yin deficiency are imbalanced in the upper respiratory tract microbiota. Treatment with methoxyphenamine and YYQFOL improves microbiota composition and alleviates symptoms.